Pseudo-dynamic testing of bridges using non linear substructuring. - Pinto, A.V.
Pseudo dynamic tests on a large scale model of an existing six pier bridge were performed at the ELSA laboratory using the substructuring technique. Two physical pier models were constructed and tested in the laboratory, while the deck, the abutments and the remaining four piers were numerically modeled on-line. These tests on a large scale model of an existing bridge are the first to have been performed considering non-linear behavior for the modeled substructure. Asynchronous input motion, generated for the specific bridge site, was used for the abutments and the pier bases. Three earthquake tests with increasing intensities were carried out, aimed at the assessment of the seismic vulnerability of a typical European motorway bridge designed prior to the modern generation of seismic codes. The experimental results confirm the poor seismic behavior of the bridge, evidenced by irregular distribution of damage, limited deformation capacity, tension shift effects and undesirable failure locations.
Keywords: Pseudo-dynamic testing; Substructuring; Asynchronous input; Existing bridge